The Introvert's Guide to Chairing the Department - Jeff Buller (Academic Chairpersons Conference Proceedings, 2020)
Most training for department chairs is based on the assumption that the best leaders are extraverts: They have good social skills, love to keep an open-door policy, and are available 24/7. But a surprising percentage of academics, including many department chairs, are actually introverts. How can they become effective leaders? This workshop provides practical training.
Keywords: introverts extrovert extravert departmentchair academicleadership leadership leadershipstyle